Study of genetic diversity in rice (Oryza sativa L.) - K. PARIMALA, K.RUKMINI DEVI, C.CHERALU and (The Journal of Research, PJTSAU, 2017)
Rice (Oryza sativa L.) is an important cereal crop and food for more than half of the world population. There is a need to increase the rice production to meet the demand of ever growing population. The rice germplasm is a rich reservoir of valuable genes that plant breeders can harness for crop improvement. A thorough understanding of the genetic structure and diversity of rice varieties is crucial for efficient utilization of rice genetic resources. Genetic divergence is an efficient tool for selection of parents for hybridization programme. The more diverse the parents, the greater are the chances of obtaining higher amount of heterotic expression in F1s and broad spectrum of variability in segregating generations (Vivekananda and Subramaniam 1993). Keeping this in view, fortyfive rice genotypes wereevaluated to assess the genetic diversity ofgenotypes forfurther utilization in breeding programmes.